The Bilingual Native Speaker Competence: Evidence From Explicit and Implicit Language Knowledge Using Elicited Production, Sentence-Picture Matching, and Pupillometry - Scherger, Anna-Lena; Urbanczik, Gianna; Ludwigs, Timon; Kizilirmak, Jasmin M. (Frontiers in Psychology, 2021)
The present pilot study investigated potential effects of early and late child bilingualism in highly proficient adult bilinguals. It has been shown that some early second language (eL2) speakers stagnate when it comes to complex linguistic phenomena and that they display subtle difficulties in adulthood. Therefore, we have chosen the complex structure of double object constructions. We investigate the long-term achievement in a combined-method approach using elicited production, explicit comprehension by sentence-picture matching and a measure of implicit linguistic knowledge, namely pupillometry. This eye tracking method is suitable for measuring implicit reactions of the pupils to unexpected or ungrammatical stimuli. For production, ditransitive structures were elicited by means of a game. For comprehension, a sentence-picture matching task was conducted. Two pictures were shown on a monitor that were equal with respect to the involved objects, but the thematic roles of direct and indirect objects were interchanged. Items were controlled for length, gender, animacy, semantic likelihood and word order. Reaction times and accuracy scores were analyzed. To this end, N = 18 bilingual adult speakers of German (+ another language, mean age: 26.5) with different ages of onset participated in this study and were compared to N = 26 monolingual German adult speakers (mean age 23.9). All participants had a proficiency of German above 89% correct in placement and cloze tests. Results show fully comparable productive and comprehensive competencies in monolinguals and bilinguals including the reaction times in the sentence-picture matching task and a robust effect of word order on the reaction times in both groups. In the pupillometry task, we found monolinguals and bilinguals to be sensitive to differing conditions with respect to grammatical and strongly ungrammatical utterances. However, we find between group differences in pupil dilations in that bilinguals react differently to strong grammatical violations than monolinguals. These results are discussed with respect to the term of native speaker competence and the variation within both groups.